IL-7 signalling represses Bcl-6 and the TFH gene program - Paul W. McDonald (Nature Portfolio, 2016)
It remains incompletely understood how cytokines shape TH1 cell differentiation to central memory T (TCM) and follicular T helper (TFH) cells. Here the authors show that TH1 cells can co-initiate the expression of both TFH and TCM gene programs and that IL-7 signalling represses TFH-associated but not TCM-associated genes.